Spectroscopic analysis on the phenolic constituents from garcinia mangostana / Shaari Daud ...[et al.] - Daud, Shaari; Ruseli, Nurulhuda; Mohamed Azlan, Siti Aisyah; Harith, Siti Suhaila; Ee, Gwendoline Cheng Lian; Zamakhshshari, Nor Hisam (Universiti Teknologi MARA Cawangan Pahang, 2018)
The Garcinia mangostana was belong to Clusiaceae family and usually found in subtropical countries. This plant was rich with phenolic compounds that showed good biological activities such as antitumor, anti-malarial, anti-inflammatory, antiviral and antioxidant. Study on the G. mangostana has been done in order to isolate these phenolic compounds. The bark and pericarp of G. mangostana were extracted with hexane and ethyl acetate for 48 hours by using cold extraction methods. Then the isolation part was done by subjected the extracts to a series of column chromatography. The pure isolated compounds confirmed their structures by spectroscopic analysis such as1H and 13C-NMR, HMBC, HMQC, DEPT and MS and comparison with literature data. Four prenylated xanthones, α-mangostin, β-mangostin, garcinone D (pericarp) and 9-hydroxycalabaxanthone (bark) were isolated from the G. mangostana.